Racial/Ethnic Variation in All-Cause Mortality among U.S. Medicaid Recipients with Systemic Lupus Erythematosus: An Hispanic and Asian Paradox - Gómez-Puerta, José A. (Arthritis Rheumatol, 2015)
OBJECTIVE: Incidence of systemic lupus erythematosus (SLE) is disproportionately high in non-Whites vs. Whites. However, variation in mortality according to race/ethnicity has not been well studied. We examined all-cause mortality by race/ethnicity among SLE patients in Medicaid. METHODS: Within the Medicaid Analytic eXtract 2000–2006 from 47 U.S> states and D.C., we identified individuals aged 18–65 years, enrolled for ≥3 months, with ≥ 3 claims for SLE (ICD-9 710.0), each ≥ 30 days apart. Lupus nephritis (LN) was identified by ≥ 2 additional claims for glomerulonephritis, proteinuria, or renal failure. We calculated mortality rates (MR) per 1,000 person-years with 95% confidence intervals by race/ethnicity. Multivariable Cox regression models estimated mortality risks, adjusting for age, sex, demographics and comorbidities. RESULTS: Among 42,221 prevalent SLE patients, 8,191 had LN. Blacks represented 40.1%, Whites 38.4%, and Hispanics 15.3%. Overall SLE MRs per 1000 person-years were highest among Native Americans (27.52), Whites (20.17) and Blacks (24.13), and lower among Hispanic (7.12) or Asian SLE patients (5.18). After multivariable adjustment, Hispanic and Asian patients had lower mortality risks [HR 0.48 (95%CI 0.40–0.59) and 0.59 (95%CI 0.40-0.86)] vs. Whites. Conversely, risks for death were significantly higher among Native American (HR 1.40, 95%CI 1.04–1.90) and Black (HR 1.21, 95%CI 1.10–1.33) compared to White patients. Among LN patients, mortality risks were lower among Hispanic and Asian patients (by 56% and 40%) than among Whites. CONCLUSION: After accounting for demographic and clinical factors, Asian and Hispanic SLE Medicaid patients had lower mortality than did Blacks, Whites or Native American patients.